Production of Ergot Alkaloids by Fermentation Method - Rawal, T. N.; Ali, S. E.; Agarwal, P. N. (Defence Science Journal, 2014)
Capacity of three strains of the fungus, Claviceps purpurea to produce ergot alkaloids from synthetic media has been investigated. Of the three strains studied, Claviceps purpurea received from Prairie Regional Laboratory, Saskatoon, Canada gave high yields of ergot alkaloids. The effect of different carbohydrates, nitrogen sources and precursors on the production of ergot alkaloids has been studied. Highest yield (2.287 gm/1) of the total alkaloids has been obtained with maltose as a carbohydrate source, ammonium succinate as a nitrogen source and tryptophan (500 mg/1) as a precursor.